Do entretenimento à crítica: letramento multimodal crítico no livro didático de inglês com base em gêneros dos quadrinhos - Predebon, Nathalia Rodrigues Catto (2015)
The concepts of multimodality and genre and a critical perspective on language have been recurrent in contemporary debates, both in the local context (BRASIL, 2006; MOTTA-ROTH, 2008b; NASCIMENTO, 2012; to name a few) and global (COPE; KALANTZIS, 2000, 2008, 2012; KRESS, 2003; JEWITT, 2005, 2008; O'HALLORAN, 2008, to name a few). However, little is known about how to implement these concepts through explicit and interrelated ways in the pedagogical context. Informed by the concept of recontextualization of these concepts, related to current knowledge of language science, this study aimed at investigating to what extent and how activities based on comics genres offer potential to promote what I call critical multimodal literacy for English teaching. Based on the proposal of Critical Genre Analysis (MOTTA-ROTH, 2008b), by combining a language theory based on a systemic functional and a social semiotic approach, a genre-based pedagogical perspective and a critical approach to language, I intend to verify critical multimodal literacy practices in English textbooks, part of the National Textbook Program for Modern Foreign Language in high school level education (BRASIL, 2009b, 2011). In order to meet the objective of the research: 1) the contexts of production, circulation and consumption of the textbooks, considered under the concept of genre, were investigated in search of references to the concepts of genre, multimodality and critical literacy (guided by the perspective of multiliteracies), which theoretically and methodologically associated generate a proposal for critical multimodal literacy; 2) activities that explore comics genres were selected and analyzed on the basis of linguistic and contextual strata of Systemic Functional Linguistics exploited in combination with epistemic moves which describe the analytical and pedagogical objectives of the activities; 3) contextual and textual data were combined to interpret and explain to what extent and how the activities have the potential to promote critical multimodal literacy. The results showed that the activities offer great potential to explore practices of critical multimodal literacy, although they lack systematic application of the concepts of multimodality and critical literacy. Occurrences of activities were observed across all strata, although the visual semiotic resources were usually explored in graphic and lexicogrammatical strata. Although fewer occurrences of activities focused on the analysis of the contextual stratum of discourse were identified, there is potential for expansion of the discussions, as the teacher s guide and the evaluation presented in the Textbooks Guide indicate. In this sense, the emphasis lies in the role of teachers as language experts and key players in the educational process and not in the textbook. The textbook functions as a mediator genre of social practices of the school context, which appears to be displaced from the center of this process, as one of many discursive practices which recontextualize discourses from language science in the educational context.